2016
DOI: 10.1111/jocn.13253
|View full text |Cite
|
Sign up to set email alerts
|

A lesbian, gay, bisexual and transgender dedicated inpatient psychiatric unit in rural New England: a descriptive analysis in demographics, service utilisation and needs

Abstract: Context in which sensitive questions are asked may affect the accuracy of demographic data. Lack of information regarding patients' sexual orientation or gender identity may impact perceived need for culturally competent care. Results suggest the need for efforts to provide training for mental health specialists in rural areas to provide sensitive care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…The homophobia levels of the nurses who work in hospital 2 were the lowest, and this may be related to the fact that this institution is located in the city center and provides service to people with higher educational levels and a more diverse population of patients. A study found that the locations of institutions have positive or negative effects on levels of homophobia (Klotzbaugh & Glover, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The homophobia levels of the nurses who work in hospital 2 were the lowest, and this may be related to the fact that this institution is located in the city center and provides service to people with higher educational levels and a more diverse population of patients. A study found that the locations of institutions have positive or negative effects on levels of homophobia (Klotzbaugh & Glover, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…31,32 It is important for clinicians to become well versed on the diversity within these communities and to consider that adolescents, elderly, and racial/ethnic sexual minority clients may have additional needs (e.g., additional minority stressors and discrimination). 33,34 There are opportunities to incorporate suicide prevention efforts into primary care medical settings, where most individuals receive services prior to their suicide. 35 In some cases, culturally competent programming has been incorporated in medical schools to inform providers about interacting with LGBT patients.…”
Section: Discussionmentioning
confidence: 99%
“…[24][25][26][27] Studies of psychiatric treatment utilization among transgender people are sparse. [28][29][30][31][32] In one San Francisco-based study, despite higher prevalence of physical and mental health problems and psychopharmacology use among transgender people compared with cisgender people, there was no difference between transgender and cisgender people in emergency room visits, outpatient emergency behavioral health care utilization, or psychiatric hospitalizations. 28 Although this finding could reflect more appropriate utilization of nonemergent care, a plausible and concerning alternate conclusion is that transgender patients are not accessing care when they need it, perhaps due to fears of misgendering and mistreatment.…”
Section: Introductionmentioning
confidence: 99%